Analysis Factors Influencing Lecturer at the Universitas Pembangunan Nasional “Veteran” Jawa Timur Using And Receiving E-Learning Based on Age With Unified Theory of Acceptance and Use of Technology Model - Firza Prima Aditiawan; Henni Endah Wahanani (Future Science)
Implementation of e-learning at the UPN “Veteran” of East Java began in 2004 but not yet the existing study program uses consistently because in its implementation is still constrained some technical and non-technical problems. To find out why these problems occur, we need analysis of behavioral factors of usage and acceptance of e-learning which is limited by age and the model used is Unified Theory of Acceptance and Use of Technology. The final outcome of the age factor acceptance and use model shows that all proposed hypotheses are accepted, so that the factors influencing the lecturers of the UPN “Veteran” of East Java in acceptance and use of e-learning are Performance Expectation, Effort Expectancy, Social Influence, Facilitating Condition, Behavior Intention, and Use Behavior.